KEAHLIAN FORENSIK, INDEPENDENSI, PENGALAMAN DAN SKEPTISME PROFESIONAL PADA KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN - Mukoffi, Ahmad; Ren, Nofrida Herlinda; Ekasari, Luh Dina (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2023)
The purpose of this study is to evaluate how forensic knowledge, independence, experience, and professional skepticism affect auditors' capacity to detect fraud in Public Accounting Firms (KAP) in Malang City. Ten questionnaires are sent to each firm of auditors in KAP Malang as part of the data gathering technique. Descriptive statistics, data quality checks, conventional assumption tests, and hypothesis testing are all components of data analysis. The study's findings suggest that forensic knowledge has no impact on auditors' capacity to detect fraud, and independence, experience, professional skepticism influence the audiotr’s ability to detect fraud.